LEAF ANATOMY AND ESSENTIAL OIL PRODUCTION IN NATIVE SPECIES OF LIPPIA - Oliveira, Ariana Reis Messias Fernandes de; Oliveira, Lenaldo Muniz de; Carneiro, Joseane Silva; Silva, TÃ¢nia Regina dos Santos; Costa, Larissa Correa do Bonfim (REVISTA DE AGRICULTURA, 2019)
This work aimed to perform a comparative study of leaf anatomy, trichome frequency and essential oil production of some Lippia native species of the semi-arid region of Bahia, Brazil. Leaf samples were analyzed with light microscopy and scanning electron microscopy to describe the structure and to quantify the trichome frequency. Six types of glandular trichomes were identified: uni, bi and tetracellular, as well as three types of tectorial trichomes. L. bromleyana presents an ornamented epidermis and no tectorial trichomes on the abaxial surface. L. thymoides has glandular trichomes with irregular contours on both leaf faces, with a higher frequency of tectorial trichomes on the adaxial surface and peltate glandular trichomes on the abaxial surface. L. insignis and L. lasiocalycina are anatomically similar, and present a higher tector trichome frequency on the abaxial surface compared to the others species. L. thymoides and L. insignis are distinguished by the essential oil production.Â 